Is the Neutrophil-to-Lymphocyte Ratio Associated With Increased Morbidity After Colorectal Surgery?. Issue 1 (February 2019) - Benlice, Cigdem; Onder, Akin; Babazade, Rovnat; Hrabe, Jennifer; Stocchi, Luca; Steele, Scott; Gorgun, Emre
Abstract : Purpose: We aimed to evaluate the association between preoperative and postoperative neutrophil-to-lymphocyte ratio (NLR) and 30-day postoperative complications after colorectal surgery. Methods: Patients undergoing elective colorectal surgery between January, 2010 and December, 2014 were identified. Patients who had preoperative and postoperative days 1 and 2 (Postoperative day [POD]-1, POD-2) NLR were included in the study. Primary study outcomes were optimal NLR cutoff values at preop, POD-1, and POD-2. Results: A total of 1328 patients met the inclusion criteria. Of those, 518 (39%) patients experienced at least one postoperative complication. Sex ( P <0.001), diabetes mellitus (DM) ( P <0.001), diagnosis ( P =0.001), operation type ( P =0.03), and open surgery ( P <0.001) were statistically associated with higher NLR (POD-1, P =0.02; POD2, P =0.01). DM (OR, 1.97; 95%CI, 1.27-3.08; P =0.003] and NLR on POD-2≥9.2 (OR, 1.43; 95%CI, 1.03-1.98; P =0.02) were significantly related to postoperative complications. Conclusions: NLR may provide clinicians with an additional tool for identifying patients at high risk for postoperative complications after elective colorectal surgery. Routine use of NLR may lead to early intervention and potentially improve the management of complications after colorectal surgery.